2007
DOI: 10.1016/j.ijpsycho.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials during an emotional Stroop task

Abstract: Emotional Stroop tasks have gained wide interest in scientific literature in the last two decades. Although no direct measure of attention is employed, these studies infer the presence of preferential processing of threatening information based on reaction time (RT) impairment in a competing task. Because event-related potential (ERP) measures are sensitive to both the extent (amplitude) and speed (latency) of cerebral processing, they are valuable tools with which to examine more directly the claim that threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(234 citation statements)
references
References 72 publications
20
206
7
1
Order By: Relevance
“…In the present study, MDD participants had larger P1 and P3 amplitude for sad faces in the positive priming condition compared with the other groups, while they had smaller P3 amplitude for sad faces in the negative priming condition, which suggested that the MDD participants had deficient distracter inhibition and excessive facilitation of negative stimuli. Furthermore, enhanced and reduced N1, P1, and P3 amplitude of depression in different conditions was observed mainly at the parietal (P4) and occipital (O2) electrodes, which is largely consistent with previous ERP studies on cognitive inhibition in healthy populations (Kathmann et al, 2006;Zhu et al, 2010;Thomas et al, 2007;Ceballos et al, 2003). In a recent first study combining the NAP task with ERP in MDD, it was also found that MDD participants had reduced central-parietal P2 amplitude for negative experimental trials, which is suggestive of cognitive disinhibition (Yao et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, MDD participants had larger P1 and P3 amplitude for sad faces in the positive priming condition compared with the other groups, while they had smaller P3 amplitude for sad faces in the negative priming condition, which suggested that the MDD participants had deficient distracter inhibition and excessive facilitation of negative stimuli. Furthermore, enhanced and reduced N1, P1, and P3 amplitude of depression in different conditions was observed mainly at the parietal (P4) and occipital (O2) electrodes, which is largely consistent with previous ERP studies on cognitive inhibition in healthy populations (Kathmann et al, 2006;Zhu et al, 2010;Thomas et al, 2007;Ceballos et al, 2003). In a recent first study combining the NAP task with ERP in MDD, it was also found that MDD participants had reduced central-parietal P2 amplitude for negative experimental trials, which is suggestive of cognitive disinhibition (Yao et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Broyd et al, 2005, Dimoska and Johnstone, 2007, Dimoska and Johnstone, 2008, Dimoska et al, 2003, Smith et al, 2004, Smith et al, 2006, Smith et al, 2008, Thomas et al, 2007, Watson et al, 2005 which reduces the number of statistical comparisons made while optimally allowing for differences in the anterior-posterior and hemispheric dimensions (Picton et al, 2000, Smith et al, 2004, Watson et al, 2005.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is also involvement of these early ERP components in cognitive paradigms, such as Location-based Priming (Gibbons et al 2006;Kathmann et al 2006) and emotional Stroop (S. J. Thomas et al 2007) tasks. To better understand the inhibitory processes that are linked to this early time window, we analyzed data from the ERP studies that were conducted with inhibitory paradigms, such as the Go/No-go, Stop-signal and Eriksen Flanker paradigms.…”
Section: Erps For Inhibition In the First 200 Msmentioning
confidence: 99%